F(x+9)=2(x+9)-9

Simple and best practice solution for F(x+9)=2(x+9)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x+9)=2(x+9)-9 equation:


Simplifying
F(x + 9) = 2(x + 9) + -9

Reorder the terms:
F(9 + x) = 2(x + 9) + -9
(9 * F + x * F) = 2(x + 9) + -9
(9F + xF) = 2(x + 9) + -9

Reorder the terms:
9F + xF = 2(9 + x) + -9
9F + xF = (9 * 2 + x * 2) + -9
9F + xF = (18 + 2x) + -9

Reorder the terms:
9F + xF = 18 + -9 + 2x

Combine like terms: 18 + -9 = 9
9F + xF = 9 + 2x

Solving
9F + xF = 9 + 2x

Solving for variable 'F'.

Move all terms containing F to the left, all other terms to the right.

Reorder the terms:
-9 + 9F + -2x + xF = 9 + 2x + -9 + -2x

Reorder the terms:
-9 + 9F + -2x + xF = 9 + -9 + 2x + -2x

Combine like terms: 9 + -9 = 0
-9 + 9F + -2x + xF = 0 + 2x + -2x
-9 + 9F + -2x + xF = 2x + -2x

Combine like terms: 2x + -2x = 0
-9 + 9F + -2x + xF = 0

The solution to this equation could not be determined.

See similar equations:

| z/8=10.2 | | 3-tan^2b=0 | | 20x^2-55x=0 | | F(x+9)=2(x+9) | | 8/12=24/? | | 22x^2+99x=0 | | G=(p-9)180 | | 4/5=?/20 | | 16x^2+72x=0 | | -7/9x | | l+x=1 | | 2(-4x+9y+6xy)-5(2x+8y)= | | x-.15x=20600 | | -3=-14+x | | 4x-12+1=-7x-12+1 | | 2(2p+3)=p+9 | | -4(x-3)-x-5=-5(x+6)+13 | | 9+-3x=8x+-3x | | 18x-12=8x+16 | | 2760.25/x=2.41 | | 2(2n+1)=3n+8 | | -x-3+4+2x-5=0 | | (6x^4/y)^2 | | 5-2x-3x-7=0 | | 1+-5x=5+8x | | 15(v+4)-3v=4(3v+3)-17 | | g(x)=1/3f(x-4) | | LN=3x+25 | | -0.10(126)+0.90x=0.05(x-14) | | 3x^2=-10x-6 | | 57-3n=21 | | 7[z-(5z+18)+2]=3(z+4) |

Equations solver categories